HUBUNGAN GREEN PRODUCT DAN GREEN AWARENESS TERHADAP PURCHASE INTENTION MELALUI CUSTOMER ATTITUDES DI SURABAYA - Beatrice, Jesslyn; Sidharta, Helena (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The research aims to examine the relationship between green product (GP) and green awareness (GA) on purchase intention (PI) through customer attitude (CA) in Surabaya. Using a quantitative approach, data was collected through a questionnaire survey to 316 respondents who focused on consumers of environmentally friendly cosmetic products. The results showed that GP has a positive influence on CA and PI. Meanwhile, GA also has a positive effect on CA and PI. Even more, CA plays a mediating role in linking GP and GA to PI. Important implications can be taken out from the finding related to moving in relation to consumer attitudes, environmental awareness, and eco-friendly products, thereby affecting purchase behavior decision-making and consumer loyalty. This study suggests that companies need to increase environmental education and develop sustainable green products to motivate consumer purchase intention.